ANALYZING SYMPTOMS AND CAUSING FACTORS OF SPEAKING ANXIETY IN ENGLISH PRESENTATIONS AMONG UNIVERSITY STUDENTS - Juwaidah, Afrida; Pauzan, Pauzan; Rahmat, Hery; Khusniyah, Nurul Lailatul; Hisyam, Ibnu (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
Speaking anxiety is a significant challenge faced by students in English presentations. Students who experience anxiety during presentations exhibit various symptoms and influenced by multiple factors. This study aims to analyze the symptoms and causal factors of speaking anxiety among a state university students, particularly those participating in the English Camp organized by the English Study Club. This research employs a qualitative descriptive approach to explore students' experiences related to speaking anxiety. Data were collected through semi-structured interviews, observations, and questionnaires during the English Camp. The questionnaire was adapted from the Foreign Language Classroom Anxiety Scale (FLCAS) to identify students with high levels of anxiety. Selected students were then interviewed and observed to identify the symptoms and factors contributing to their anxiety. The findings that speaking anxiety manifests in observable symptoms, categorized into physical symptoms (trembling, a pale face and rigid facial expression), verbal symptoms (voice shaking, frequently using filler words), and observable symptoms in the form of action. Meanwhile, non-observable symptoms include nervousness; heart palpitations; difficulty in thinking, forgetting material, and mind blank; experiencing a cold sensation. The primary causing factors of students’ speaking anxiety include lack of vocabulary, lack of preparation, lack of practice, fear of making mistakes and being laughed at, fear of being the focus of attention and memory disassociation.